IMPACTS OF FEEDING UREA ON RUMEN FERMENTATION, TOTAL NUMBER OF BACTERIA AND SOME BLOOD PARAMETERS IN SHAMI GOATS - Ibrahim, Salam Shaban; Tawfeeq Al-ani, Jamal Abdul Rahman; Al-Wazeer, Anmar Abdulghani Majeed; Shaker, Rasha Mohamed (Emirates Journal of Food and Agriculture, 2021)
To follow up the effects of feeding urea on rumen characteristics, rumen bacteria and some blood parameters in Shami goats, after 21 days of feeding 1.5% urea with concentrated feed, rumen fluid was collected at different times 0, 1, 2, 3 and 6 hours after morning feeding, pH were measured, some of rumen fluid was used for bacterial count, while 0.1N HCL was added to other part and kept in deep freeze for measuring rumen NH3-N and volatile fatty acids. Sixteen male Shami goats were distributed to T1 without urea and T2 1.5% urea. Rations fed at 3% of body weight as DM basis and alfalfa hay was fed ad-libitum. After 90 days, Jugular blood was sampled. Results showed no significant effects of feeding urea to Shami goats on blood parameters, while, rumen NH3-N decreased (p<0.05) for urea treatment after 3h of feeding with increasing volatile fatty acids (VFA) and pH values(p<0.05) of rumen fluid at 3h and 6h after feeding. Bacteria counts decreased at 0, 3 and 6h after feeding at dilution 107 and 109 CFU/ml, due to ingestion large amounts of water with urea treatment and increase rate of passage of bacteria and rumen contents to other parts of alimentary canal.